In vitro bioactivity and biocompatibility of magnesium implants coated with poly(methyl methacrylate) - bioactive glass composite. (December 2022) - Rouein, Zanko; Jafari, Hassan; Pishbin, Fatemehsadat; Mohandes, Fatemeh; Simchi, Abdolreza
Abstract: Magnesium (Mg) and its alloys have proved promising as biodegradable candidates for the repair of bone tissue. Despite the encouraging bio-related properties of Mg, its high corrosion rate in contact with body fluids still presents a major challenge. An efficient approach to address this issue is to provide a protective coating on Mg. The present research evaluates, for the first time, in vitro bioactivity and biocompatibility of a novel multifunctional composite coating based on poly(methyl methacrylate) (PMMA) biopolymer and bioactive glass (BG) particles on Mg-based implant. Electrophoretic deposition (EPD) was utilized to obtain this coating from a bi-component suspension. Coatings' morphological analyses by scanning electron microscopy established that EPD provides a facile route for simultaneous deposition of the biopolymeric matrix and BG in the form of a dense and homogeneous coating on the surface of Mg. Chemical characterizations of the coatings performed by energy-dispersive spectroscopy and FT-IR spectroscopy confirmed the presence of both PMMA and BG components in the composite film. In vitro acellular bioactivity test in simulated body fluid (SBF) verified bone-like apatite formation on coatings due to the presence of BG particles. Additionally, in vitro cellular cytotoxicity using MTT assay demonstrated cellular viability in contact with the composite coatings. Moreover, the corrosion behavior of the pure Mg vs coated Mg samples in SBF was assessed electrochemically using linear polarization and impedance spectroscopy techniques. A significant increase in the polarization resistance from 65.89 Ω.cm 2 for uncoated Mg to 1365.1 Ω.cm 2 for Mg coated with a composite film (obtained from 45 g/L PMMA and 3.5 g/L BG suspension) was observed. This indicated a reduction of 95.17% in the corrosion rate of Mg substrate by application of a composite coating. The dramatic reduction in Mg substrate corrosion rate accompanied by in vitro bioactivity and cytocompatibility of the developed composite, reflect the high potential of the present strategy in the modification of Mg-based implants for successful bone tissue engineering applications. Graphical Abstract: ga1 Highlights: Novel bioactive and corrosion-resistant composite coating on Mg biomedical implant. PMMA facilitates bioactive glass deposition via a facile electrophoretic method. Composite coatings were bioactive due to apatite formation in simulated body fluid. 95.17% reduction in corrosion rate in composite-coated Mg vs bare Mg. Coatings supported the growth of MG63 cells and were non-cytotoxic.